La réception du catholicisme au féminin dans les cultures amérindiennes canadiennes (XVIIe - XXe siècles) - Marion Robinaud (Centre de Recherches sur les Mondes Américains, 2015)
The object of this paper is to identify, across time and space, the means by which the First Nations of Canada have been able to adopt the Catholic religion through a feminine prism. After having shown that the spirituality of the religious congregations was chiefly oriented around Catholicism’s feminine figures, the author demonstrates the existence of similarities between traditional rituals of First Nations people and Catholic rituals that may shed light on the amazing strength of these feminine devotions within the practices of First Nations people since the 17th Century.  The example of Catherine Tekawhitka, a Mohawk Indian woman who lived in the second half of the 17th Century and was canonized in 2012, evidences the special link between women and the Catholic First Nations’ faith spread across the centuries.